Model Of Rational And Emotional Decision Making In The First Purchase Of Cosmetics - Elly Yuliandari Yuliandari; Gugus Wijonarko; Amaliyah; Mazzlida Mat Deli (TIJAB (The International Journal of Applied Business), 2023)
Background: Consumers face both positive and negative impacts when buying a product for the first time. Existing studies emphasize the rational aspects in making decisions to buy cosmetics. Buying cosmetics will include liking the product (emotional aspect) and the good effects obtained from buying the product, in addition to rational considerations such as product safety (rational aspect). This study aims to determine the effect of cognitive and emotional orientation models in making decisions to buy cosmetics for the first time. Objective: This study examines the rational and emotional aspects of buying a cosmetic product for the first time. Method: This research involved 131 consumers who either bought cosmetics for the first time or a new product. Consumer age ranges were from 18 to 22 years. Respondents have used cosmetics for up to 3 years. Respondents were selected using accidental sampling. Results: showed that rational and emotional considerations significantly contribute to purchasing decisions. Consumers not only consider the benefits of these cosmetics, but also pay attention to their feelings towards these products. Conclusion: Consideration of emotional and rational aspects will influence purchasing decisions. The preferences and positive expectations consumers feel will be a more dominant factor than fear of risk. Producers need to communicate information that can make consumers happy in addition to product functions. Keywords: Ratio Considerations, Emotional Considerations, Purchasing Decision-making